2019
DOI: 10.1371/journal.pone.0217069
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of crop rotational diversity and grazing under integrated crop-livestock system on soil surface greenhouse gas fluxes

Abstract: Integrated crop-livestock (ICL) system is beneficial in enhancing soil organic carbon and nutrient cycling. However, the benefits of the ICL system on mitigation of GHG emissions are poorly understood. Thus, the present study was initiated in 2011 to assess the effect of crop rotation diversity and grazing managed under the ICL system on GHG emissions. The cropping system investigated here included spring wheat grown continuously for five years and a 5-yr crop rotation (spring wheat-cover crops-corn-pea/barley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 61 publications
6
23
0
1
Order By: Relevance
“…These results are similar to those reported by Abagandura et al. () and Linn and Doran (). The lowest N 2 O emissions (0.165 ± 0.002 g N 2 O‐N ha −1 h −1 ) occurred in the early winter which corresponded to low soil moisture contents (0.234 ± 0.014 cm 3 cm −3 ) and low CO 2 ‐C (285 ± 67 g CO 2 ‐C ha −1 h −1 ), whereas the highest emissions occurred in the early spring when soil moisture and CO 2 emissions were high.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are similar to those reported by Abagandura et al. () and Linn and Doran (). The lowest N 2 O emissions (0.165 ± 0.002 g N 2 O‐N ha −1 h −1 ) occurred in the early winter which corresponded to low soil moisture contents (0.234 ± 0.014 cm 3 cm −3 ) and low CO 2 ‐C (285 ± 67 g CO 2 ‐C ha −1 h −1 ), whereas the highest emissions occurred in the early spring when soil moisture and CO 2 emissions were high.…”
Section: Resultssupporting
confidence: 93%
“…The correlation analysis between the individual components shows that N 2 O-N emissions were influenced by both soil temperature and soil moisture (Table 7). Others have reported similar findings (Abagandura et al, 2019). However, our research also showed that while temperature is correlated to N 2 O emissions, this relationship may be positive in the fall and negative in the spring (Figure 4).…”
Section: Relationship Among Temperature Moisture and N 2 O And Co 2supporting
confidence: 86%
See 1 more Smart Citation
“…The cumulative CH 4 fluxes in the 2013, 2014, and 2015 seasons under biochar and manure treatments for the two soils are shown in Table 2. No significant differences were observed in cumulative CH 4 fluxes from biochar and manure treatments in both soils (Table 2), perhaps due to the similar soil water content among treatments (Abagandura et al, 2019). Kammann et al (2012) and Wang et al (2012) also reported no significant effect of biochar on soil CH 4 fluxes compared with the CNT in the dryland cropping system.…”
Section: Resultsmentioning
confidence: 94%
“…Wagle and Kakani (2014) and Wegner et al (2018) also reported CO 2 peaks as a response to heavy precipitation. It is likely that heavy precipitation in 2014 increased microbial activity and C mineralization, causing an increase in CO 2 flux (Abagandura et al, 2019; Sainju et al, 2008, 2010).…”
Section: Resultsmentioning
confidence: 99%